Profiling ocular surface responses to preserved and non‐preserved topical glaucoma medications: A 2‐year randomized evaluation study. (27th July 2020) - Mohammed, Imran; Kulkarni, Bina; Faraj, Lana A.; Abbas, Ali; Dua, Harminder S.; King, Anthony J.
Abstract: Background: Use of topical glaucoma medications has been reported to cause ocular surface (OS) discomfort and inflammation. This study explores the profile of inflammatory cytokines and OS symptoms induced in response to preserved and non‐preserved drops. Methods: Prospective, randomized evaluation on 36 treatment‐naïve patients over 24 months of three differently preserved glaucoma drop preparations: Preservative‐free (PF), polyquad (PQ) and benzalkonium chloride (BAK). Study participants were evaluated at baseline and then at 1, 3, 6, 12 and 24 months while on medication. At each visit, participants completed the OS disease index (OSDI) questionnaire, had basal tear sampling and impression cytology (IC) of the conjunctival epithelium. Quantitative polymerase chain reaction was performed to measure the gene expression of inflammatory cytokines [interleukin (IL)‐6, IL‐8, IL‐10, IL‐12A, IL‐12B, IL‐17A, IL‐1β and tumour necrosis factor‐α] in the IC samples. Corresponding protein expression of cytokines in tear samples was assessed by the Becton‐Dickinson cytometric bead arrays. Results: Compared to PF and PQ groups, mRNA and protein expression of IL‐6, IL‐8 and IL‐1β increased in samples from the BAK group in a time‐dependent fashion, whereas all other cytokines showed a non‐significant increase. In the BAK group, there was a strong correlation between OSDI and the levels of IC/IL‐1β ( r = .832, R 2 = .692 and P = .040); IC/IL‐10 ( r = .925, R 2 = .856 and P = .008) and tear/IL‐1β ( r = .899, R 2 = .808 and P = .014). Conclusions: BAK‐preserved topical drops stimulate a sterile inflammatory response on the OS within 3 months which is maintained thereafter, whereas PF‐drops and PQ‐preserved drops showed no significant OS inflammation.